1994
DOI: 10.1073/pnas.91.23.10898
|View full text |Cite
|
Sign up to set email alerts
|

The aged monkey basal forebrain: rescue and sprouting of axotomized basal forebrain neurons after grafts of encapsulated cells secreting human nerve growth factor.

Abstract: Six Rhesus monkeys between 24 and 29 years of age received unilateral transections of the fornix. Three monkeys then received intraventricular transplants of polymer-encapsulated baby hamster kidney (BHK) fibroblasts that had been genetically modifled to secrete human nerve growth factor (hNGF). The remaining three monkeys received identical grafts except the cells were not modified to secrete hNGF.Monkeys receiving the fornix transection and control grafts displayed extensive reductions in the number of choli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(72 citation statements)
references
References 23 publications
3
69
0
Order By: Relevance
“…NGF also induces sprouting of cholinergic fibres. 4,6 As shown in Figure 3b, we observed a significant increase in sprouting of p75NGFR-immunoreactive fibres around devices with NGF-producing cells. Quantification by image analysis showed significantly more sprouting around devices with NGC0211 cells (2.281 ± 0.142 mm 2 p75NGFR-immunoreactive area per section) than around devices with ARPE-19 cells (0.349±0.027 mm 2 per section) and NGC-0295 cells (1.186 ± 0.063 mm 2 per section), Po0.05.…”
Section: Ngc0211 Cells Secrete High Amounts Of Correctly Processed Ngfsupporting
confidence: 58%
“…NGF also induces sprouting of cholinergic fibres. 4,6 As shown in Figure 3b, we observed a significant increase in sprouting of p75NGFR-immunoreactive fibres around devices with NGF-producing cells. Quantification by image analysis showed significantly more sprouting around devices with NGC0211 cells (2.281 ± 0.142 mm 2 p75NGFR-immunoreactive area per section) than around devices with ARPE-19 cells (0.349±0.027 mm 2 per section) and NGC-0295 cells (1.186 ± 0.063 mm 2 per section), Po0.05.…”
Section: Ngc0211 Cells Secrete High Amounts Of Correctly Processed Ngfsupporting
confidence: 58%
“…16 To investigate if regulated delivery of neurotrophic factors has effects on neuronal rescue and axonal growth in vivo, we utilized a well-established model of basal forebrain neuron degeneration, the fim- bria-fornix transection, which mimics the cholinergic component of cell loss in Alzheimer's disease. 3,9,[18][19][20][21] Following fimbria-fornix lesions, cholinergic neurons of the medial septal nucleus undergo degeneration over a 2-week period; this degeneration is entirely prevented by grafts of NGF-secreting cells adjacent to the degenerating somata; 3,9,17,22 further, the grafts become penetrated by cholinergic axons, providing an assay of axonal growth responses.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, BDNF is also involved in the development of motor coordination (Strand et al, 2007). Several studies have demonstrated that age-and AD-related dysfunctions of the cholinergic system related to physical activity as well as cognitive function are ameliorated by NGF and BDNF treatment (Williams et al, 1986;Casamenti et al, 1994;Kordower et al, 1994;Murray et al, 1994).…”
mentioning
confidence: 99%